High respiratory syncytial virus burden in children under 3 years of age across all care levels in England. - Carter,EC; Hill,H; Solórzano,C; Kerruish,L; McLellan,L; Dodd,J; Smith,AB; Joseph,A; Lewis,D; Fyles,F; Drysdale,SB; Gonzalez-Dias,P; et al. (BMJ Open Respir Res, 2026)
OBJECTIVES: This prospective surveillance study aimed to estimate the burden of laboratory-confirmed respiratory syncytial virus (RSV) in under 3-year-olds in the United Kingdom. SETTING: The study was implemented in Merseyside and Bristol, encompassing 11 primary care sites, 5 walk-in centres, 2 secondary care hospitals and 2 tertiary care hospitals. PARTICIPANTS: Children aged under 3 years presenting with lower respiratory tract infection (LRTI) symptoms were included, with a substudy in primary care recruiting children with upper respiratory tract infection (URTI). PRIMARY AND SECONDARY OUTCOME MEASURES: The primary outcome of the study was the prevalence of RSV infection in primary, secondary and tertiary healthcare settings. Secondary outcomes included severity outcomes (rates of hospitalisation and high dependency care admissions), risk factors for severe disease, economic burden of disease and coinfection prevalence. RESULTS: 2000 children were included in the analysis (410 primary care and 1590 secondary/tertiary care). 318 were included in the URTI substudy. RSV prevalence was 50.0% (95% CI 46.7% to 53.3%) in children admitted to hospital via emergency departments (ED), 36.3% (95% CI 31.7% to 41.0%) in ED discharges, 36.5% (95% CI 24.7% to 49.6%) in primary care (LRTI) and 12.7% (95% CI 8.6% to 17.9%) in primary care URTI. Healthy term-born children accounted for 70.1% of RSV hospitalisations. Risk factors for severe disease included any level of prematurity, age <3 months and congenital cardiac disease. RSV-positive cases incurred a higher mean cost per participant (£1811, 95% CI £1720 to £1903) than RSV-negative cases (£1295, 95% CI £1220 to £1370). CONCLUSIONS: The findings revealed a substantial burden associated with RSV. Even moderate prematurity was a risk factor for severe disease, and these children may not benefit from maternal RSV vaccination due to missed late gestation antibody transfer. Fur